Chemical signals and reconstruction of life strategies from ancient human bones and teeth – problems and perspectives - Szostek, Krzysztof (Anthropological Review, 2009)
Chemical analyses of historical and prehistoric bone material provide us with a complex body of knowledge in bioarcheological studies. These can be used for reconstructing diet, migration, climate changes and the weaning process. The analysis of enamel, dentin and bones allows researchers to gather data on life strategies of an individual by retrospectively tracing his ontogenetic phases. This is made possible through knowledge of the mineralization periods of permanent and deciduous teeth while simultaneously taking account of differences between enamel, dentin and bone remodelling rates, dependent on the age of the individual. Yet, the large interpretative potential of isotope analyses of bone material is severely limited by diagenesis. The accurate recording of diagenetic changes in historical human bone material is a current main trend in bioarcheological research. Today, a highly specialised set of research tools is used for verifying whether bones unearthed at archeological sites are suitable for isotope tests. Isotope determinations are pivotal in this research as reconstructions of paleodiets or migrations of our ancestors can be based only on material that has been maintained intact in sufficient proportions post mortem.